Analisis Mekanisme Pengungkapan Kasus Penipuan Investasi Di Masyarakat Pada Masa Pandemi Covid 19 (Studi Kasus Polda Daerah Istimewa Yogyakarta) - Ulfaturrahmi Ulfaturrahmi; Hendi Yogi Prabowo; Umi Wahidah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to identify trends in investment fraud problems during the Covid 19 pandemic, identify disclosure mechanisms carried out by the Yogyakarta Regional Police in investment fraud cases, explore the obstacles encountered in disclosing investment fraud cases and provide recommendations for improvements that can be made by the Regional Police. Yogyakarta Special. This research was conducted to analyze the role of the Regional Police of the Special Region of Yogyakarta in disclosing cases of investment fraud during the Covid 19 pandemic by using the crime triangle. This study used a qualitative approach using primary and secondary data from the Special Region of Yogyakarta Regional Police, while collecting data by means of documentation and in-depth interviews. The results of the study show that the cause of investment fraud is due to the low financial literacy of the community so that people are easily persuaded by the large benefits offered. The role of the Regional Police of the Special Region of Yogyakarta in disclosing cases of investment fraud in the community during the Covid-19 pandemic was carried out through the stages of complaint, investigation and investigation. Keywords : The role of Polda, Disclosure, Investment, Covid 19